γδ T-cell lymphoma: a rare entity mimicking hemophagocytic syndrome-report of two cases - Maheshwari, Ujwala; Mahore, Kalyani; Pereira, Evith; Dhar, Reeta (International Journal of Research in Medical Sciences, 2017)
γδ T-cell lymphoma is a rare extranodal and systemic neoplasm which accounts for less than 1% of all NHL having peak incidence in adolescents and young adults with a male predominance. Study report two cases, 29 and 25 years male presented with fever, abdominal pain and pancytopenia; one had hepatosplenomegaly while other had marked splenomegaly respectively and both showing feature of hemophagocytosis. Both underwent splenectomy. On gross examination, the spleen was markedly enlarged and shows a deep brown cut-surface. Histologically the normal structure of the spleen is totally effaced by a monotonous lymphoid population consisting of medium-large sized lymphoid cells with vesicular chromatin and small eosinophilic nucleolus with tumor cells showing moderate amount of eosinophilic cytoplasm. Liver biopsy showed regenerative changes in parenchyma and sinusoidal involvement by tumour cells. Peripheral smear revealed atypical lymphocytes with pancytopenia. Bone marrow aspiration showed moderate neoplastic infiltrate by lymphoid cells. Immunophenotypic study showed tumour cells expressing CD3, CD56, CD 2 (dim), TIA-1, TCR-gamma. The tumour cells were immunonegative for CD20, CD5, CD4, CD8, granzyme B, CD7, CD10 and CD 23. Immunophenotypic study is must for diagnosis of γδ T-cell lymphoma which can mimic hemophagocytic syndrome.